Valine derived poly (acetylenes) as versatile chiral lyotropic liquid crystalline alignment media for RDC-based structure elucidations - Krupp, Alexis (Magnetic resonance in chemistry : MRC, 2021)
© 2020 The Authors. Magnetic Resonance in Chemistry published by John Wiley & Sons Ltd.